2021
DOI: 10.1371/journal.pone.0248230
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an admission coagulation panel for risk stratification of COVID-19 patients

Abstract: Background There is limited data on the markers of coagulation and hemostatic activation (MOCHA) profile in Coronavirus disease 2019 (COVID-19) and its ability to identify COVID-19 patients at risk for thrombotic events and other complications. Methods Hospitalized patients with confirmed SARS-COV-2 from four Atlanta hospitals were included in this observational cohort study and underwent admission testing of MOCHA parameters (plasma d-dimer, prothrombin fragment 1.2, thrombin-antithrombin complex, fibrin mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 12 publications
0
6
0
2
Order By: Relevance
“…In contrast, the current new risk model comprises high risk substrates for embolism, such sex and history of embolism, and multidimensional evaluation of the general condition of the infection (D-dimer, CRP, radiographic congestion on radiographs, and the need for intubation) that together allow early prediction of embolic complications in COVID-19. The AUC of the new risk model was 0.83, which is higher than that of MOCHA (0.74) and indicates the superior diagnostic performance of our model [24] . Moreover, among high-risk patients with COVID-19 and CVDRF, the predictive value of MOCHA for adverse events has not been validated to date.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In contrast, the current new risk model comprises high risk substrates for embolism, such sex and history of embolism, and multidimensional evaluation of the general condition of the infection (D-dimer, CRP, radiographic congestion on radiographs, and the need for intubation) that together allow early prediction of embolic complications in COVID-19. The AUC of the new risk model was 0.83, which is higher than that of MOCHA (0.74) and indicates the superior diagnostic performance of our model [24] . Moreover, among high-risk patients with COVID-19 and CVDRF, the predictive value of MOCHA for adverse events has not been validated to date.…”
Section: Discussionmentioning
confidence: 62%
“…If the infection site in patients with symptomatic COVID-19 is limited on the lung alveoli at admission, the initiation of systemic inflammation by the release of cytokines—such as interleukin-(IL-)1β, IL-6, and tumor necrosis factor-α, which are known to induce thromboembolism—may not occur [23] . Recently, a new risk scoring system has been proposed, titled “markers of coagulation and hemostatic activation” (MOCHA); its predictive value for arteriovenous thromboembolism in patients with COVID-19 was reportedly superior to that of D-dimer alone [24] . However, the parameters selected for this scoring system, including plasma D-dimer, prothrombin fragment 1.2, thrombin-antithrombin complex, and fibrin monomer levels, are not routinely evaluated in daily clinical practice, and the feasibility of using this system is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…A consequente trombose macrovascular, seja arterial ou venosa, associada a um contexto de paciente acamado a longo prazo, aumenta o risco de complicações graves como trombose venosa profunda (TVP), embolia pulmonar (EP), infarto do miocárdio e acidente vascular encefálico (AVC ou AVE), mesmo em pacientes submetidos à anticoagulação profilática ou terapêutica (COMINO-TRINIDAD et al, 2021;ALABYAD et al, 2021).…”
Section: Resultsunclassified
“…Assim, por ser uma doença inflamatória com tendências trombóticas, existem muitos esforços da comunidade científica para compreender a doença e sua coagulopatia associada, mas ainda há muito para esclarecer sobre o seu mecanismo e a forma como o sistema hemostático desempenha um papel no desenvolvimento desta doença e suas complicações (ALABYAD et al, 2021). Dado essa necessidade, esse estudo busca realizar uma revisão integrativa de literatura acerca da relação entre COVID-19 e a ocorrência de alterações hemostáticas associadas a distúrbios no sistema de coagulação sanguínea.…”
Section: Referênciasunclassified
“…These recommendations are based on several studies that have shown a high incidence of TE complications, both pulmonary embolism and deep vein thrombosis, in hospitalized patients with COVID-19 disease. In fact, the incidence of venous thromboembolism in these patients seems to range from 24% to 27%, which means that about one third of patients with COVID-19 will have an episode of venous thromboembolism during the disease [27,57]. The incidence of pulmonary embolism is about 16.5%, while that of deep vein thrombosis varies from 7% to 14%.…”
Section: Which Antithrombotic Treatment Is the Most Appropriate?mentioning
confidence: 99%